Development of Discovery Learning Student Worksheets to Improve Students' Critical Thinking Skills in Chemical Balance Materials - Andi Ulfa Tenri Pada; Ainur Rizki; Ibnu Khaldun (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the quality of Discovery Learning Student Worksheets to improve students' critical thinking skills and increase students' Critical Thinking Skills on chemical equilibrium material. This study uses research development methods with the design of the Borg and Gall models. The samples in this study were 140 students of Al-Falah Islamic Senior High School Aceh Besar to develop Student Worksheets and 61 people of IT Al-Fitiyan Senior High School to implement Discovery Learning Student Worksheets. The instruments used were questions and student response questionnaires. The data analysis technique uses the percentage equation and analysis of students' critical thinking skills improvement using the N-gain equation and independent-sample t-test. The results showed that the quality of the Discovery Learning Student Worksheets could improve students' critical thinking skills on chemical equilibrium material, as evidenced by the results of the quality assessment of the Discovery Learning Student Worksheets from the validation results obtained an average of 79% with a decent category. The analysis of students' critical thinking skills proves that there is a difference in the average critical thinking skills of students before and after applying the Discovery Learning Student Worksheet on chemical equilibrium material with a Sig value. (2-tailed) < 0.05. The results obtained prove that the use of Discovery Learning Student Worksheets is better than conventional Student Worksheets in improving students' Critical Thinking Skills.